2020
DOI: 10.1002/cam4.3424
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of transvaginal sonoelastography for differential diagnosis between malignant and benign cervical lesions: A systematic review and meta‐analysis

Abstract: Background To evaluate the performance of transvaginal sonoelastography (TVSE) for differential diagnosis between malignant and benign cervical lesions using a meta‐analysis. Methods An independent literature search was conducted on the English medical database, including PubMed, Embase and Medline, Cochrane Library, Web of Science, and OVID. The diagnostic accuracy of TVSE was compared with that of histopathology, which is the gold reference standard for diagnosis. The accuracy of TVSE was assessed by calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They had derived an aggregated diagnostic odds ratio for TVSE, which was 21.42 (95 percent CI 13.65-33.61), with sensitivity at 0.87 (95 percent CI 0.84-0.90), the specificity at 0.79 (95 percent CI 0.72-0.84), and the AUC was 0.892 (Q* = 0.822). Meta-regression analysis report found that imaging approach as well as the method of evaluation and QUADAS score were not significant (all having P > 0.05), ultimately having no impact on research variability [14]. This study was pioneered by an effort to increase literature material on TV strain elastography material in cases presenting with masses of cervix.…”
Section: Empirical Reviewmentioning
confidence: 98%
“…They had derived an aggregated diagnostic odds ratio for TVSE, which was 21.42 (95 percent CI 13.65-33.61), with sensitivity at 0.87 (95 percent CI 0.84-0.90), the specificity at 0.79 (95 percent CI 0.72-0.84), and the AUC was 0.892 (Q* = 0.822). Meta-regression analysis report found that imaging approach as well as the method of evaluation and QUADAS score were not significant (all having P > 0.05), ultimately having no impact on research variability [14]. This study was pioneered by an effort to increase literature material on TV strain elastography material in cases presenting with masses of cervix.…”
Section: Empirical Reviewmentioning
confidence: 98%